Effect Of A Mixture Of Lime, Alum, And Ferrous Chloride With Different Doses To Improve Peat Water Quality - Rahmi, Aulia; Budijono, Budijono; Purwanto, Eko (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractPeat water generally has an acidic pH, brownish-red color, and high turbidity. To improve the quality of peat water, coagulation-flocculation processing can be carried out. The types of coagulants used are lime, alum, and ferric chloride. This study aims to determine the effect of a mixture of lime, alum, and ferric chloride at different doses on improving the quality of peat water. Water samples were taken from Kualu Nenas Village, Tambang District, Kampar Regency, and Riau. This study used an experimental method with a completely randomized design. There were 4 treatments and 3 replications. Each treatment has a water volume of 1 liter with a settling time of 20 minutes. The data obtained were analyzed using Analysis of Variance (ANOVA) with SPSS ver 17.0 software. If there is a real effect, then the Duncan's Multiple Range Test (DMRT) level of 5% is carried out. The treatments applied were, P1 (0.50 g lime + 0.41 g alum + 0.45 g ferric chloride), P2 (0.50 g lime + 0.476 g alum + 0.336 g ferric chloride), P3 (0.50 g ferric chloride). g lime + 0.544 g alum + 0.224 g ferric chloride, P4 (0.50 g lime + 0.612 g alum + 0.112 g ferric chloride). Based on the results obtained, it can be concluded that a mixture of lime, alum, and ferric chloride can improve the quality of peat water The best treatment was found in P1 0.50 g lime + 0.41 g alum + 0.45 g ferric chloride with pH measurements of 7.6, turbidity 2.28 NTU, color 44.7 Pt / Co and organic matter 49, 3 mg / L. Keyword: Coagulation, Flocculation, pH, Peat waterand Turbidity